ANALYSIS OF TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE CAPABILITIES OF TADRIS SCIENCE TEACHER PROSPECTIVE STUDENTS AT UIN FATMAWATI SUKARNO BENGKULU - Sisi Mulia Utami; Meirita Sari; Sukarno Sukarno (Universitas Bhinneka PGRI, 2024)
This research aims to describe the Technological Pedagogical Content Knowledge abilities of Tadris Science Teacher Candidate Students at Fatmawati Sukarno State Islamic University, Bengkulu. This research is a type of Mixed Methods research which combines quantitative and qualitative methods. The overall research results show that the abilities of Tadris Natural Sciences students at Fatmawati Sukarno Bengkulu State Islamic University are relatively good with an average percentage of 80.5%. It can be concluded that the level of Technological Pedagogical Content Knowledge ability of Tadris Science teacher candidates as a whole is relatively good with an average score of Technological Knowledge 80.9%, Pedagogical Knowledge 78.9%, Content Knowledge 81.3%, Technological Content Knowledge 80.6 %, Pedagogical Content Knowledge PCK 80.4%, Technological Pedagogical Knowledge 80.9% and Technological Pedagogical Content Knowledge 80.5%.